Estudos biológicos de cochonilhas do gênero Planococcus (Hemiptera: Pseudococcidae) em diferentes hospedeiros - Correa, L.R.B.; Souza, B.; Santa-Cecilia, L.V.C.; Prado, E. (My University, 2011)
This work was carried out to study the development of populations of the genus Planococcus in different plant species, aiming at the verification of host specificity. The mealybugs Planococcus minor were obtained from cocoa plants (Theobroma cacao L.) and coffee crop (Coffea canephora L.), and Planococcus citri from citrus seedlings (Citrus sinensis L. Osbeck). Single eggs were transferred to Petri dishes containing leaf discs of cocoa (T. cacao cultivar Catongo), coffee (Coffea arabica L. cultivar Mundo Novo) and citrus (C. sinensis cultivar Pera Rio). They were maintained on a water-agar slide at 1%, with the abaxial surface turned upwards. The dishes were sealed with a PVC plastic film and kept in climatized chambers regulated at 25 [plus or minus] 1[degrees] C, 70 [plus or minus] 10% RH and 12 hours of photophase. For the mealybugs coming from cocoa plants, the citrus substrate prolonged the nymphal development of the males (26.0 days). In the nymphal period of females and males coming from coffee plants, the coffee substrate allowed a shorter duration of that period (19.2 and 21.3 days, respectively) and, in addition to having providing a longer longevity to the females (59.1 days). The highest rates of mortality were obtained when they were reared on the cocoa substrate, regardless of the host plant from which they were originally collected, and when kept on citrus, for insects collected on coffee plants. P. citri and P. minor have higher preference for coffee substrate regardless of the original host, thus showing partial host specificity.

Este trabalho teve por objetivo estudar o desenvolvimento de populações de cochonilhas do gênero Planococcus em diferentes espécies vegetais, visando à verificação de especificidade hospedeira. A cochonilha Planococcus minor foi obtida de plantas de cacau (Theobroma cacao L.) e de café (Coffea canephora Pierre), enquanto Planococcus citri foi obtida de plantas de citros (Citrus sinensis L. Osbeck). Ovos foram transferidos individualmente para placas de Petri contendo discos foliares de cacau (T. cacao cultivar Catongo), café (Coffea arabica L. cultivar Mundo Novo) e citros (C. sinensis cultivar Pêra Rio), utilizando-se 60 repetições. Esses discos foliares foram mantidos sobre uma lâmina de ágar-água a 1%, com a superfície abaxial voltada para cima. As placas foram vedadas com filme plástico de PVC e mantidas em câmaras climatizadas reguladas a 25 ± 1º C, 70 ± 10% UR e 12 horas de fotofase. Para as cochonilhas oriundas de cacaueiro, o substrato citros prolongou o desenvolvimento ninfal dos machos (26,0 dias). Para os insetos provenientes de cafeeiro, o substrato café proporcionou o menor período ninfal de fêmeas e machos (19,2 e 21,3 dias, respectivamente) e maior longevidade das fêmeas (59,1 dias). Os maiores índices de mortalidade foram obtidos quando as cochonilhas foram criadas no substrato cacau, independente da planta hospedeira da qual foram originalmente coletadas, e quando mantidas em citros, a partir de espécimes coletados em plantas de café. Há maior preferência alimentar de P. citri e P. minor para o substrato café, independente do hospedeiro de origem, o que indica uma especificidade hospedeira parcial.
Biologic studies of mealybugs of the genus Planococcus (Hemiptera:Pseudococcidae) on different hosts